2016
DOI: 10.1016/j.msea.2015.12.075
|View full text |Cite
|
Sign up to set email alerts
|

Deformation behavior of multilayered NiFe with bimodal grain size distribution at room and elevated temperature

Abstract: We describe a study of the temperature dependent deformation behavior of a multilayered NiFe-60wt%Fe alloy with a layer thickness of 5 μm fabricated by electrodeposition. The structure of adjacent layers alternates between a nanocrystalline and a coarse grained. Uniaxial tensile tests at temperature between 20˚C and 400˚C and strain rate of 10-4-10-2 were used to determine the mechanical behavior. Microstructure observations via transmission electron microscopy and fractography were performed to provide insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…In this method, two or more alternative layers that have different compositions and properties are used [7]. Compared to the monolithic coating method, due to the high hardness of the layers and graded microstructures, the surface properties such as mechanical, electrochemical, optical and oxidation resistance are signi cantly increased [8] [9] [10]. Also, composite multilayer coatings not only have lower shear stress but also show a good ability to prevent crack growth, which increases the lifetime properties of the part [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this method, two or more alternative layers that have different compositions and properties are used [7]. Compared to the monolithic coating method, due to the high hardness of the layers and graded microstructures, the surface properties such as mechanical, electrochemical, optical and oxidation resistance are signi cantly increased [8] [9] [10]. Also, composite multilayer coatings not only have lower shear stress but also show a good ability to prevent crack growth, which increases the lifetime properties of the part [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, microstructure-modulated MLs add crystal size as a new dimension to scaling relationships in MLs. Early studies on the mechanical properties of microstructure-modulated MLs are reported by Chan et al [21], Lavernia and coworkers [22][23][24], and Daly et al [25] for architectures comprised of alternating nanocrystalline (NC) and coarsegrained (CG) layers. While these initial studies have revealed the mechanical behavior of ML with modulated microstructures, a broader understanding of the interplay between crystal size and layer thickness (i.e., multiple independently controlled size effects) is currently lacking.…”
Section: Introductionmentioning
confidence: 99%